Natural leather car upholstery - characteristics and sewing challenges - Rogina-Car, Beti (Array, 2019)
This paper gives an overview of materials and specifics in production of upholstery for vehicles. Special attention has been paid to natural leather as one of the most luxurious materials for the manufacture of car interior upholstery materials. Its properties, advantages and disadvantages are compared with textile materials. The quality of suitable seams is one of the most challenging tasks in making upholstery. In this paper, special emphasis is placed on cutting and sewing natural leather used for making car interior upholstery. Natural leather is a specific natural material that gives a touch of luxury to car seats and interiors. Durability, high price and lower market offer of leather lead to its restricted use for car upholstery compared to textile materials; however, these reasons in particular make it extremely desirable at the same time. According to previous research, cutting and sewing of leather car upholstery require greater attention also when choosing the appropriate leather, sewing machine, thread, needle and seam type, which will give satisfactory properties of the car upholstery in all segments. The purpose of this paper is to contribute to professional knowledge and specifics related to natural leather, its use for car seats and the proper quality of the sewn seam.